Peran Self Leadership Dalam Meningkatkan Work Engagement Pada Freelance - Salsabilla Rahma Octavia; Fajar Tri Utami (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2026)
This study aims to examine the relationship between Self-leadership and Work-engagement among freelancers. Self-leadership refers to an individual‘s ability to lead themselves through goal-setting, self- reinforcement, and other self-regulation strategies. Meanwhile, Work- engagement is a positive psychological state characterized by vigor, dedication, and full absorption in one‘s work. This research employed a quantitative approach with a correlational method. The participants consisted of 214 freelancers selected through purposive sampling. Data were collected using two instruments: the Self- leadership Questionnaire (SLQ) and the Utrecht Work-engagement Scale (UWES), both of which had been tested for validity and reliability. The results revealed a significant positive correlation between Self- leadership and Work-engagement, with a correlation coefficient of r = 0.718 (p < 0.01). Furthermore, regression analysis showed that Self- leadership contributed 51.6% to the variance in Work-engagement. These findings highlight the vital role of Self-leadership in enhancing Work- engagement, particularly in flexible and autonomous work environments such as freelancing.